Illicit trade and infectious diseases - Cosimo Beverelli; Rohit Ticku (World Trade Organization (WTO), 2020)
We collect a novel dataset that covers about 130 countries and the six four-digit live animal categories in the Harmonized System (HS) over a sixteen-year period, to study the link between illicit trade in live animals and threat to animal health from infectious diseases. Our results imply that a one percent increase in illicit imports in an HS four-digit live animal category is associated with a 0.3 to 0.4 percent rise in infections amongst related species in the importing country. We explore the mechanisms and find that mis-classifying or under-pricing an imported species are the channels through which illicit trade impacts animal health.
Keywords: F14; F18; I18; K42; Q57; 330; illicit trade; missing imports; disease; live animals